Influencer Communication, Online Customer Reviews, and Consumer Attitude Formation toward Purchase Intention of MS GLOW Skincare - Fajar Ari Kurniawati; Siti Dyah Handayani (INJECT (Interdisciplinary Journal of Communication), 2026)
The intensification of digital communication in the beauty and skincare industry has positioned influencer communication and online customer reviews as key mechanisms in shaping consumer attitudes and purchase intentions. In the context of MS GLOW skincare, this study examines how influencer communication and online customer reviews function as persuasive digital messages that contribute to consumer attitude formation and subsequent behavioral outcomes. Specifically, this study analyzes the roles of influencer credibility, influencer attractiveness, and online customer reviews in shaping customer attitudes, as well as the mediating role of consumer attitude in the formation of brand awareness, brand loyalty, and electronic word-of-mouth (e-WOM) leading to purchase intention. Using a quantitative approach, data were collected from 260 MS GLOW consumers in Central Java and the Special Region of Yogyakarta and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that online customer reviews play the most influential role in consumer attitude formation, while influencer credibility does not show a significant effect, and influencer attractiveness exhibits a negative effect. Consumer attitude emerges as a central communicative outcome that strengthens brand awareness, brand loyalty, and e-WOM, with brand loyalty and e-WOM directly driving purchase intention. These findings emphasize that purchase intention is shaped through a communication process in which meaning is negotiated via influencer communication and peer-based reviews rather than through influencer attributes alone.